Sociodemographic and dietary influences on perceptions of eating habits in Jamaica - Althea La Foucade; Samuel Gabriel; Christine Laptiste; Charmaine Metivier; Vyjanti Beharry; Ewan Scott; Karl Theodore (Pan American Health Organization, 2022)
Objective. To evaluate how sociodemographic factors and food intake affect survey respondents' perceptions of the quality of their diet. Methods. This cross-sectional analysis is based on a nonprobability sample of 374 participants in Jamaica aged ≥18 years. The three-stage process used a simple random sample to select three parishes; the main commercial areas of each parish were chosen for sampling. To ensure the inclusion of a cross-section that was as representative as possible, the sample included both public and private sector businesses, such as those in retail, hospitality and tourism as well as nongovernmental organizations. Employees and patrons completed a questionnaire regarding their food consumption and their perception of their own diet. Multiple correspondence analysis was used to evaluate the nonlinear relationships among the variables. The results of the analysis guided the specification of a multivariate logistic regression model that was used to estimate the relationship between sociodemographic factors, food intake and perceived eating patterns. Results. The average predicted probability of perceiving a diet as unhealthy was reduced when the respondent was male, economically active, in good health, and married or in a common-law relationship. The probability of perceiving a diet as unhealthy was increased for respondents with a college degree and those living in ahousehold that had a male as the sole head. Consuming healthful food and drink reduced the perception of having a poor diet and vice versa, indicating there are possibly connections between food intake, the perception of diet quality and actual diet quality. Conclusions. This exploratory analysis established links between perceived diet quality, eating habits and sociodemographic factors. The impact on the perception of diet quality can be negative or positive, depending on the variable under consideration.